Audio-Visual Integration of Emotional Information - Bergman, Penny; Västfjäll, Daniel; Tajadura-Jiménez, Ana (i-Perception (London), 2011)
Emotions are central to our perception of the environment surrounding us (Berlyne, 1971). An important aspect in the emotional response to a sound is dependent on the meaning of the sound, ie, it is not the physical parameter per se that determines our emotional response to the sound but rather the source of the sound (Genell, 2008), and the relevance it has to the self (Tajadura-Jiménez et al 2010). When exposed to sound together with visual information, the information from both modalities is integrated, altering the perception of each modality, in order to generate a coherent experience. In emotional information this integration is rapid and without requirements of attentional processes (De Gelder, 1999). The present experiment investigates perception of pink noise in two visual settings in a within-subjects design. Nineteen participants rated the same sound twice in terms of pleasantness and arousal in either a pleasant or an unpleasant visual setting. The results showed that pleasantness of the sound decreased in the negative visual setting, thus suggesting an audio-visual integration, where the affective information in the visual modality is translated to the auditory modality when information-markers are lacking in it. The results are discussed in relation to theories of emotion perception.